MushÌ„aÌ„rakah and MudaÌ„rabah Instruments: Assessing their Characteristics (International Journal of Banking and Finance, 2013)
Until very recently, equity financing is more in line with the spirit of Islam as compared with debt financing. As such, mushaÌ„rakah and mudaÌ„rabah are the preferred modes for Islamic investors. It is therefore a matter of a concern that even after four decades after Islamic finance captured the attention of investors around the globe, these two purest genres account only for a small percentage of Islamic financial industry. The paper examines more searchingly for the reasons why mushaÌ„rakah and mudaÌ„rabah occupy such insignificant place among Islamic financial products. This paper offers an analytical insight.